Atrial fibrillation – Can HbA1c levels really predict the risk?. (February 2022) - Narayan, Pradeep; Mandal, Chandan Kumar; Das, Rajlakshmi; Das, Debasis; Ghorai, Paramita Auddya; Chowdhury, Saibal Roy; Das, Mrinalendu
Background: Diabetes is associated with higher mortality and worse post-operative outcomes in patients undergoing coronary artery bypass grafting and HbA1c levels have consistently been reported to be associated with adverse post-operative outcomes. However, the role of HbA1c still remains unclear with regards to the occurrence of atrial fibrillation. Method: Data for the patients undergoing off-pump coronary artery bypass grafting was analysed in a retrospective fashion. Patients were divided into–those with HbA1c < 6.5% and those with HbA1c ≥ 6.5% and the incidence of atrial fibrillation observed in these two groups. We also compared patient who developed atrial fibrillation in the post-operative period and compared them with those who did not. Results: Of the 5259 patients included in the study HbA1c was <6.5 in 2808 (53.4%) patients and was ≥6.5 in 2451 (46.6%) patients; 623 (11.8%) patients in our study developed atrial fibrillation. Onset of atrial fibrillation in the post-operative period was seen most commonly 235 (38.3%) on between 24 and 48 h after the operation with more than half of them 338 (54.2%) occurring within the first 48 h. On multivariate analysis, HbA1c was not a risk factor for atrial fibrillation (odd's ratio 1.144, 95% confidence interval 0.967–1.354). Only increased age (odd's ratio 1.08; 95% confidence interval 1.069–1.091); EuroSCORE (odd's ratio 1.073; 95% confidence interval 1.048–1.099); history of recent MI (odd's ratio 0.768; 95% confidence interval 0.606–0.971) and peripheral vascular disease (odd's ratio 1.667; 95% confidence interval 1.091–2.517) were found to be independently associated with increased risk of atrial fibrillation in the post-operative period. Conclusions: After adjusting for confounders HbA1c levels do not independently predict risk of atrial fibrillation after off-pump coronary artery bypass grafting.